Eliminating compressed air leaks in production process on compressor machine using TRIZ decision making – A case study in Somaliland company - Nagib Ismail Ahmed; Rizal Justian Setiawan; Khakam Ma’ruf; Mubarik Abdikadir; Keisa Abdi Mohamed (Universitas Muhammadiyah Magelang, 2025)
In Somaliland, electricity is an expensive necessity. The high expense of electricity presents challenges for industrial development in Somaliland. Existing industries must operate efficiently to survive, specifically in the manufacturing sector, which relies heavily on electrical machinery. The compressor is widely used in manufacturing to provide the air supply to production machines, including CNC machines. However, in some cases, the air supply from the compressor is not supplied efficiently due to air leakage in standby mode. This research aims to solve this issue by implementing an integrated system that reduces energy waste caused by compressed air leakage during standby mode. This research is grounded in the application of the TRIZ contradiction matrix, which identified Inventive Principle #28 (Mechanics Substitution) as a potential solution. The proposed solution was subsequently implemented and evaluated using a pilot experimental method within the context of a case study conducted at a manufacturing company located in Hargeisa, Somaliland. The result led to the successful implementation and testing of a control system that integrated the operations of the compressor machine and CNC machine. Compared to the conventional ball valve components, the new system replaced it with an automatic air control valve integrated with the CNC machine emergency button. Electricity consumption on the compressor machine was observed and calculated for twelve months before improvement and twelve months after implementing the improvements. The data was collected for a total of 24 months to compare before improvements and after improvements for each 12 months in a machine. The improvements showed a significant reduction in electricity consumption, from 10,982 kWh to 9,830 kWh representing 10.49% energy savings, and reduced electricity operating costs by SOS 605,952 (USD 1,067) in 12 months.